Arquitetura como projeto social Os casos dos centros de educação unificada (CEUs) em São Paulo, Brasil e dos Parques bibliotecas em Medellin, Colômbia. - Soares, Patricia de Palma (2013)
This work aims to understand how architecture can contribute as a modifying element socioeconomic, through an intervention of degraded areas lacking basic infrastructure. The research aims to focus on the study of buildings that house educational and cultural activities and their impact on the urban environment in which they operate, in case of Centros Educacionais Unificados - CEU's (Unified Educational Centers), in São Paulo, and Parques Bibliotecas (Parks and Libraries) in Medellin, Colombia. In both cases, the study sought to understand the relationship of the building with its surroundings, especially with regard to the appropriation of users through the complex and changing urban landscape, access to infrastructure and equipment for culture and leisure, favoring the reduction in the violence and improving the quality of life of local people.